IN VIVO HEPATOPROTECTIVE ACTIVITY OF CASSIA AURICULATA POLYMER NANOSPHERES CONTAINING SILYMARIN - Sagar, A. Keerthi; Devala Rao, G. (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: Hepatoprotective activity of herbal drugs has an importance in the treatment of hepatic disorders, but pharmaceutically engineered products are not evolved properly to cure the liver disorders properly based on the demand and also route, target the appropriate site of action. Methods: In our present work, we have been developed a new formulation that possesses a unique nature and site specificity for targeting the disease state. Here, we examined hepatoprotective activity of Cassia auriculata polymer nanospheres containing silymarin against carbon tetrachlorideinduced hepatotoxicity in rats using at 50 mg/kg and 100 mg/kg body weight dose levels, and we have been observed that enzyme activities of serum glutamate oxaloacetate transaminase, serum glutamate pyruvate transaminase, alkaline phosphate, total protein, albumin, globulin, total cholesterol, high-density lipoprotein (HDL), glutathione (GSH), and total bilirubin were analyzed. Results: C. auriculata polymer nanospheres and silymarin produced significant (p<0.001) hepatoprotective effect by decreasing the activity of serum enzymes, bilirubin, total cholesterol, and increased levels of HDL, total protein, albumin, globulin, and tissue GSH. Conclusion: From these results, it was concluded that of C. auriculata polymer nanospheres would protect the liver cells from carbon tetrachloride from liver diseases. Keywords: Hepatoprotective activity, Silymarin, Cassia auriculata, Nanospheres.